The Innate Mind, Volume 3 2008
DOI: 10.1093/acprof:oso/9780195332834.003.0013
|View full text |Cite
|
Sign up to set email alerts
|

13 The Creative Action Theory of Creativity

Abstract: Thought is normally the precursor of action. We think first, and then we act. Most models of creative thought and creative activity make a similar assumption. They assume that creative activity is preceded by, and causally dependent upon, creative thought. This chapter, in contrast, argues for the reverse. It develops a model according to which creative thought is always preceded by, and causally dependent upon, creatively generated action schemata. And it adduces a variety of considerations in support of that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 522 publications
0
7
0
1
Order By: Relevance
“…A possible explanation is based on the creative-action theory of creativity, postulating that creative thought is always causally dependent on non-perceptual creatively generated action-schemata (Carruthers 2007(Carruthers , 2011. Whenever an action-schema is activated, commands are sent to muscles necessary to control the action, and efferent copies are simultaneously used to generate a representation of the visual and proprioceptive perception.…”
Section: Divergent Thinking Is Negatively Correlated With Gamma Functmentioning
confidence: 99%
See 1 more Smart Citation
“…A possible explanation is based on the creative-action theory of creativity, postulating that creative thought is always causally dependent on non-perceptual creatively generated action-schemata (Carruthers 2007(Carruthers , 2011. Whenever an action-schema is activated, commands are sent to muscles necessary to control the action, and efferent copies are simultaneously used to generate a representation of the visual and proprioceptive perception.…”
Section: Divergent Thinking Is Negatively Correlated With Gamma Functmentioning
confidence: 99%
“…This, in turn, lies at the bottom of any type of imagery transformation. In this way, the non-conceptual mental rehearsal of an action-schema will give rise to an imagistic thought representing the action in question and thus to a conceptual verbal creative thought (Carruthers 2007(Carruthers , 2011. Turning back to the mindfulness practitioners, using fMRI, it has been recently found that their eyes-closed resting-state mentation exhibits significantly less DMN activation and more extrinsic (visual) activation compared to controls (Berkovich-Ohana et al 2016).…”
Section: Divergent Thinking Is Negatively Correlated With Gamma Functmentioning
confidence: 99%
“…First, Carruthers (2008) argues that when novel thoughts and actions have the opportunity to be performed in concert (i.e., are intertwined or reciprocal), there will be more perceived utility in the experience, as is the case with play, dance, and athletics. Second, the more engaging a task, the more positive affect a person experiences (Abele-Brehm 1992).…”
Section: Structuring Customized Assembly Tasksmentioning
confidence: 99%
“…In this light, one can make sense of what Carruthers (2006Carruthers ( , 2008 calls "act-first," as opposed to "thought-first," behavior. For Carruthers, theorists have modeled action as the product of beliefs, as if beliefs are first thought out on the basis of Bayesian updating.…”
Section: Internal Beliefsmentioning
confidence: 99%